Bloom Taxonomy Of Educational Objectives And The Modification Of Cognitive Levels - Adesoji, Francis A (Advances in Social Sciences Research Journal, 2018)
The author is of the opinion that the Bloom taxonomy of educational objectives particularly the six cognitive levels should reflect the levels of cognitive development and thinking of students. This thinking pattern would no doubt, reflect the student’s environment and his genetic composition. In the light of this, Bloom’s cognitive levels should not be generalised and it would be better if the six levels are collapsed into low, Medium and high cognitive process.